Perancangan Teknik Kriptografi Block Cipher Berbasis Pola Permainan Tradisional Rangku Alu - Perdana Bagas Tirta Kumbara; Magdalena A. Ineke Pakereng (Maranatha University Press, 2019)
Data security is one of the most important factors in the world of Information Technology today. One way to secure data is by Block Cipher Cryptography technique. However, some cryptographic techniques have been successfully solved by the cryptanalysis so that new cryptographic algorithms need to be created. The design of Cryptography algorithms based on traditional game patterns of Rangku Alu from East Nusa Tenggara is a design of Cryptographic Block Cipher algorithms that operate in the form of bits designed with 10 rounds where each cycle contains four processes. In each round there are four patterns for the plaintext process and four patterns for the key. The fourth process is transformed with an S-Box table to get a more random ciphertext. Tests were also carried out using Avalance Effect which reached 49,38% and the correlation value where there was a change in character reached 73,44%. So the result designing Cryptographic algorithms can be used for encryption and description in text files.